Corporate Entrepreneurship, Core Competence and New Business Creation in the Alcoholic Beverage Industry - Kerrigan, Edward John (2006)
This dissertation investigates corporate entrepreneurship and core competence in the alcoholic beverage industry by focusing on the new product development (NPD) processes involved and aims to develop a theory that corporate entrepreneurship in this particular industry is especially relevant for political, demographic and competitive reasons. Based on a case study analysis of the NPD processes of four of the major drinks companies our understanding of how new products are developed is enhanced as well as the part played by the NPD process in leveraging the core competence of the firm. A secondary hypothesis is developed aimed at categorising the type of corporate entrepreneurship exhibited by the four cases and the type of NPD process best suited to each type of corporate entrepreneurship. Most importantly the case study analysis is complimented by the feedback of four major retailers in the UK on how such NPD processes might be improved and on how new products can achieve success quickly in the trade.